2008
DOI: 10.1182/blood.v112.11.2761.2761
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Effects of Dexamethasone on Lenalidomide Activity in Multiple Myeloma: Additive/Synergistic Effects on Anti-Proliferative Activity on Myeloma Cells and Antagonistic Effects on Immune Function

Abstract: Lenalidomide (Revlimid®) is approved for the treatment of previously treated multiple myeloma (MM) in combination with dexamethasone. Single agent lenalidomide has direct antiproliferative activity against MM cells and direct immunomodulatory activity via costimulation of T cell and natural killer (NK) cell responses. The ECOG Phase III trial in newly diagnosed MM (E4A03) reported that low dose (40 mg/d on days 1, 8, 15 & 22 of a 28-day cycle) dexamethasone in combination with lenalidomide showed an overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Also, high‐dose steroid treatment can increase susceptibility to infectious complications due to their immunosuppressive effects. Recent translational studies have noted an inhibitory effect of steroids on lenalidomide‐mediated natural killer (NK) cell stimulation, suggesting that steroids may compromise the efficacy of immunomodulating agents in patients with MM (Schafer, 2008; Hsu et al , 2011). This hypothesis is substantiated by a recent large phase III study that demonstrated improved survival in newly diagnosed MM patients treated with the combination of lenalidomide and low dose dexamethasone as compared to lenalidomide and high dose dexamethasone (Rajkumar et al , 2010).…”
mentioning
confidence: 99%
“…Also, high‐dose steroid treatment can increase susceptibility to infectious complications due to their immunosuppressive effects. Recent translational studies have noted an inhibitory effect of steroids on lenalidomide‐mediated natural killer (NK) cell stimulation, suggesting that steroids may compromise the efficacy of immunomodulating agents in patients with MM (Schafer, 2008; Hsu et al , 2011). This hypothesis is substantiated by a recent large phase III study that demonstrated improved survival in newly diagnosed MM patients treated with the combination of lenalidomide and low dose dexamethasone as compared to lenalidomide and high dose dexamethasone (Rajkumar et al , 2010).…”
mentioning
confidence: 99%
“…Interestingly, both CK1α and CK2 have been shown to sustain activation of important signaling pathways such as JAK/STAT, NF-κB, and PI3K/AKT [ 95 , 97 , 98 ]. IMiDs also inhibit the proliferation of PCs by inhibiting the cyclin-dependent kinase pathway through inducing P21 [ 99 ]. Moreover, IMiDs induce direct apoptosis in PCs by activation of Fas-mediated cell death [ 100 , 101 ].…”
Section: The Existing Therapies For MMmentioning
confidence: 99%